Degradation of soils around the Kattakurgan Reservoir and its impact on soil properties - Jabbarov, Zafarjon; Abdullaev, Shokhrukh; Rakhmatullaeva, Guljakhon; Abdurakhmonov, Nodirjon; Ismonov, Abduvaxob; Kalandarov, Nazimkhon; Yuldashev, Iskandar; Pulatov, Muxiddin; Mamajanova, Uktamxon; Djabborov, Shavkat (Brawijaya University, 2025)
This study investigated hydromorphic processes in soils surrounding the Kattakurgan Reservoir and examines the influence of groundwater on their physicochemical properties. Soil samples were analyzed for particle-size distribution, pH, electrical conductivity (EC), total organic carbon (TOC), and major ion content. Particle-size analysis indicated an increase in the proportion of physical clay from 41.2% to 48.3%, confirming a pronounced hydromorphic impact on soil structure in areas where the groundwater table was within the 85-155 cm range. ANOVA and regression analyses revealed strong positive correlations between sand-silt (? = 0.922) and sande-clay (? = 0.391) fractions, whereas TOC and EC exhibited statistically significant negative relationships with sand content. The results further indicated that physical clay content was substantially higher at locations near the reservoir, where hydromorphic conditions were more intense, reflecting the compaction of soil structure associated with elevated groundwater levels. Overall, these findings highlight the critical role of groundwater fluctuations in driving structural changes in soils, with direct implications for their physicochemical properties.